Maqashid Sharia Analysis of Position The Poor Commercial Sex Workers as Mustahik Zakat in Indonesia - Ramadi, Bagus; Tarigan, Azhari Akmal; Hamdani, Muhammad Faisal (JURNAL AKTA, 2025)
The purpose of this study is to describe the maqashid sharia analysis of the position of poor prostitutes as Mustahik zakat in Indonesia. Zakat is a form of economic and social concern from muzaki to mustahik. But in the current era, many groups are considered worthy of zakat but are hindered by regulations, fiqh doctrines and stereotypes regarding certain professions. Especially in reaching marginalized groups such as prostitutes. Sex workers are part of a group that is marginalized and exploited both in terms of economic, moral and social. Using the statue approach and comparative approach, this research will look at the legal regulations in Indonesia and compare with the opinions of scholars regarding the position of prostitutes and see the extent of the opportunity for zakat distribution to prostitutes by analyzing it using maqashid sharia theory. The findings of this study reveal that the distribution of zakat to poor prostitutes can theoretically be done with various schemes including training, soft skill development and business capital injection. However, there is no regulation in Indonesia that allows this either in the law or fatwa. In terms of Islamic law, there are hadith and scholarly views that allow giving zakat as long as it is to help her get out of her profession as a prostitute, not to support her. From the maqashid sharia analysis, giving zakat to prostitutes can protect; First, the soul (ḥifẓ al-nafs) by encouraging prostitutes to leave their profession as soon as possible so that they can prevent sexual diseases, violence and sexual exploitation that can threaten them. Second, honor (ḥifẓ al-'irdh) encourages recovery and rehabilitation in their social environment. Third, wealth (ḥifẓ al-māl), empowering the economy by providing training and business capital. Fourth, religion (ḥifẓ al-dīn), zakat becomes a means of da'wah to return to being a good Muslim.